Seasonal variation of soil aggregate stability, porosity and infiltration during a crop sequence under no tillage - Castiglioni, Mario Guillermo; Sasal, Maria Carolina; Wilson, Marcelo; Oszust, José Daniel (REVISTA TERRA LATINOAMERICANA, 2018)
Soil properties vary over time with soils presenting different susceptibility to runoff and erosion during the year. Under no-tillage cropping, soil physical properties could change mainly due to the climatic factor effect, crop type and wheel traff ic. The aim of this study was to analyze the seasonal variation of selected soil physical properties of an Aquic Argiudoll under no-tillage, focusing on their relationship with water partitioning between inf iltration and runoff during a typical crop sequence of the Pampean region (Argentina). The study was carried out in an agricultural f ield located at the Paraná Experimental Station of the Instituto Nacional de Tecnología Agropecuaria (INTA) in Entre Ríos province (Argentina). Soil samples were taken at six different times during the crop rotation cycle. Soil water content, bulk density, pore size distribution, structural stability and water inf iltration obtained with a rainfall simulator were determined on each sampling date. To relate the behavior of these soil properties with the previous weather conditions, we considered different climatic variables. Our results showed that there was no influence on soil physical properties of the crop type or the wetting and drying soil cycles. However, in this high silt content Argiudoll with a moderate to high contraction and expansion capacity, it was found that soil macroporosity was higher in drier soils, reducing the runoff coeff icient. Furthermore, soil structural stability also affected the inf iltration capacity of this soil during some periods, resulting in a better structure during periods of higher temperature. We conclude that the critical period for this Argiudoll to generate runoff would be mid-autumn to early spring, when the soil water content is higher, temperatures are low, and therefore macroporosity, soil structural stability and inf iltration rates have worse values. In this sense, winter cover crops is a management practice that will favor the soil drying and coverage, reducing runoff risk during this period.